2005
DOI: 10.1359/jbmr.050708
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Improves, Whereas sFlt1 Inhibits, BMP2-Induced Bone Formation and Bone Healing Through Modulation of Angiogenesis

Abstract: We studied the interaction between VEGF and BMP2 during bone formation and bone healing. Results indicate that VEGF antagonist inhibited BMP2-elicited bone formation, whereas the delivery of exogenous VEGF enhanced BMP2-induced bone formation and bone healing through modulation of angiogenesis.Introduction: Angiogenesis is closely associated with bone formation during normal bone development and is important for the bone formation elicited by BMP4. However, it remains unknown whether vascular endothelial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
317
4
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(346 citation statements)
references
References 29 publications
16
317
4
9
Order By: Relevance
“…This interactive biology is difficult to reproduce in vitro. The hallmark of this process is BMP activity; it is known and accepted that BMP-2 is the prototypical molecule for osteogenesis [50]. Terminal osteogenic differentiation is promoted by rhBMP-2; thus, abrogating BMP-induced differentiation has a robust biological basis for HO prophylaxis [32,42].…”
Section: Discussionmentioning
confidence: 99%
“…This interactive biology is difficult to reproduce in vitro. The hallmark of this process is BMP activity; it is known and accepted that BMP-2 is the prototypical molecule for osteogenesis [50]. Terminal osteogenic differentiation is promoted by rhBMP-2; thus, abrogating BMP-induced differentiation has a robust biological basis for HO prophylaxis [32,42].…”
Section: Discussionmentioning
confidence: 99%
“…Combined use of VEGF and BMP-2 [19,24,34,35,37,40] and BMP-4 [20,25,36] showed synergistic effects in osteogenesis. It has been shown that combined use of VEGF with one of the most potent BMPs, BMP-6 [23,26], enhances osteogenesis and angiogenesis of mouse bone marrow stem cells in vitro and in vivo [8], however, the effectiveness of this therapy for ON has not been determined.…”
Section: Questions/hypothesesmentioning
confidence: 95%
“…Direct VEGF administration can improve blood flow and neovascularization in necrotic bone [38]. In addition to its effects on angiogenesis, VEGF plays an important role in bone growth and repair by interacting with other growth factors [35,36]. However, overexpression of VEGF actually can adversely affect osteogenesis and decrease bone formation [25,[34][35][36][37].…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations